UNLOCKING CONCISE EXPRESSION: A GUIDE TO TEACHING PARTICIPLE CLAUSES - Safiya Solihova Azamatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Participle clauses are clear and prestige grammatical structures, which improves a sophistication of English communication. However, these participle clauses frequently challenge English language learners. Learning and teaching participle clauses empowers students to express challenging ideas with simplicity and understandability. This article will offer and provide teachers with practical and effective strategies for interactively teaching participle clauses by focusing on their function, structure, and various types.